Abusive Supervision, Intentions to Quit, and Employees' Workplace Deviance: A Power/Dependence Analysis - TEPPER, Bennett J. (Institutional Knowledge at Singapore Management University, 2009)
We conducted a two-study examination of relationships between abusive supervision and subordinates’ workplace deviance. Consistent with predictions derived from power/dependence theory, the results of a cross-sectional study with employees from three organizations suggest that abusive supervision is more strongly associated with subordinates’ organization deviance and supervisor-directed deviance when subordinates’ intention to quit is higher. The results also support the prediction that when intention to quit is higher, abusive supervision is more strongly associated with supervisor-directed deviance than with organization-directed deviance. These results were replicated in a second study, a two-wave investigation of people employed in a variety of industries and occupations.